Bridging the Gap: A Comprehensive Review of the Interrelation and Intricacies of Medical Writing with Medical Communication in a Healthcare Ecosystem - Hood, Mitesh Mohan; Sawhney, Garima; Varma, Shaloo; Goyla, Kapil (Recent Updates in Disease and Health Research Vol. 9, 2024)
In the interconnected web of the healthcare ecosystem, effective communication is of chief importance for promulgating medical knowledge, cultivating and strengthening patient engagement, as well as encouraging interdisciplinary collaboration. This review provides a detailed analysis of the interrelation and intricacies between medical writing and medical communication, exploring their roles, challenges, and evolving dynamics. Through an interdisciplinary lens, it delves into how medical writing translates complex medical information into accessible formats, while medical communication bridges the gap between healthcare providers, patients, and the broader community. By uncovering their symbiotic relationship and addressing emerging trends, this review aims to offer insights into how the seamless integration of medical writing and medical communication contributes to enhanced healthcare outcomes and societal well-being.